Does arthrodesis in the foot need to be delayed due to low vitamin D level: A retrospective study of concomitant treatment of hypovitaminosis at the time of arthrodesis - Troy J. Boffeli, DPM, FACFAS; Abimbola O. Johnson, DPM; Catlea M. Gorman, DPM, AACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2021)
Statement of Purpose: We routinely assess vitamin D preoperatively and treat low vitamin D peri-operatively, but this approach has not been studied. This retrospective case control study assesses the fusion rates of 1st metatarsal phalangeal (MPJ), 1st tarsal-metatarsal (TMT) and subtalar joint (STJ) with a stratified approach to concomitant vitamin D supplementation and fusion at the time of arthrodesis. Methodology: Retrospective review of 100 cases of 1st MPJ, TMT, and STJ fusions. Obtained serum 25-hydroxyvitamin D levels preoperatively, and recorded results in three categories: sufficient (> 30%), insufficient (20-30%), and deficient (10-20%). Insufficient levels had 2,000 IU D3 daily supplementation. Deficient levels were prescribed 50,000 IU D2 weekly x 12 weeks. Surgery was not delayed unless vitamin D was under 10%. All three categories were compared. 10-week fusion rates and average time to fusion were evaluated. Procedures: The joint preparation for all three procedures consist of curettage and burring. Fixation for the 1st MPJ included a compression screw and dorsal locking plate. Fixation for the 1st tarsal-metatarsal joint and subtalar joint fusions consisted of two screws. Results: Cases of 65 sufficient, 23 insufficient, and 12 deficient levels of vitamin D. 10-week fusion rates of 94%, 96%, and 92% respectively, with no statistical significant difference. Analysis & Discussion: Research is limited on the influence of Vitamin D in foot arthrodesis procedures. In this study, it is evident that vitamin D deficiency with per-operative supplementation can maintain high fusion rates. It remains unknown if no supplementation in these groups would produce poor healing rates.